Effect of microwave sintering treatment to the flank wear of titanium carbide tools in milling operations - Iqbal, Mohammad; Ariff, Tasnim Firdaus; Fahmi, Shahrul; Al Hazza, Muataz Hazza Faizi; Hilmy, Irfan; Suryanto, - (2014)
The paper reports the research on the improvement of tool wear resistant of Titanium Carbide (TiC) cutting tool after microwave post sintering treatment. Titanium Carbide square milling insert was microwave sintered at 600°C with 15 minutes of holding time. The face milling operations were conducted to Carbon Steel S45C block (130 mm x 95 mm x 40 mm) by using both of original and microwave sintered insert at 5 different cutting speed (60, 90 , 120 , 150 and 180 m/min), constant feed rate (0.2 mm/tooth) and constant depth of cut(0.2 mm/tooth). The flank wear of the insert was measured every nearest 10th minute of complete cutting passes. The results of the experiment show that microwave post sintering treatment improves the tool resistant of the TiC insert. The flank wear of the sintered insert is lower at any machining time and all cutting speed. The research also found that the percentage of the improvement is lower at higher cutting speed compare to lower cutting speed.